REPRESENTATIVE MODELS OF MILITARY CODES IN THE KAZAKH HISTORICAL NOVELS - Altybayeva S.М.; Comutstsi L.V. (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with representative modeling of the military code in the Kazakh historical novel. The categories of narrative convention, plausibility, generalization, proposed by S. Chatman, with reference to modern Kazakh prose are identified and explored. Military codes make up a significant amount of all cultural codes embedded in the narrative. The referential and phenomenological aspects of the semantics of military code are implemented through a system of implicit and explicit images, motives, and informative descriptions. Military codes are also interpreted in the article as variants within a culturally more extensive nomadic code. The authors claim that the modeling of military codes is a result of a complex process of interactive networking of the marked concepts, from a detailed description of weapons, uniforms and types of military units to fictional military events corresponding to the historical epoch recreated in the narrative. The military codes of specific subject-matter content are accompanied by hidden, intentionally significant mythologems, philosophems, and ideologems. For the documentary and quasi-documentary narratives, the effect of credibility and viability of the presented events, participants and situations is caused by the immersion into the historical context of the work the recipient is supposed to be familiar or unfamiliar with. Establishing associative-allusive connections causes a particular kind of evocation, namely that of “awakening” of the reader’s historical memory and of his awareness of the deep continuity with the past. A typology of the military codes of modern Kazakh historical fiction is proposed. It embraces historiosophemes, historical ethnonyms and toponyms, historical realities, philosophems and ideologemes, mythologems, rituals, naming titles of the military, political and priestly hierarchy. The article was written as part of the grant project AP05133019 funded by the CS of the MES RK.